The development of practice standards for patient education in nurse-led clinics: a mixed-method study - Zohre Pouresmail; Fatemeh Heshmati Nabavi; Maryam Rassouli (BMC, 2023)
Abstract Introduction Educating patients and families about self-care is one of the important roles of nurses in Nurse-led clinics (NLCs). NLCs need standards for guiding the practice of nurses. A standard is an authoritative statement that sets out the legal and professional basis of nursing practice. This paper seeks to report the development of practice standards for patient and family education in NLCs. Methods This project used a Sequential-Exploratory mixed methods design. Before the study, we conducted a literature review to identify gaps. Directed content analysis was used in phase 1. The second phase involved two focus groups. The third phase involves two rounds of modified Delphi. Results Twenty-nine participants were interviewed, and 1816 preliminary codes were formed in phase 1. 95 standards were grouped into three main categories (structure, process, and outcome). In the first focus group, experts eliminate 32 standards. Experts eliminate 8 standards after the second stage of the focus group. After two rounds of Delphi, the final version of the standard consists of 46 standards (13 structure, 28 process and 5 outcome). Conclusions Nurses and institutions could benefit from practice standards for patient education in the NLCs, which consist of 46 statements in three domains, as a guide for clinical activities and a tool to gauge the quality of patient education in NLCs. The developed standards in this study can guide new and existing NLCs and help them evaluate ongoing activities. Providing patient education in NLCs based on standards can improve patients' outcomes and promote their health.